„Library Network Support Services: modernising libraries in Armenia, Moldova and Belarus through library staff development and reforming libraries [LNSS]” (Confluenţe Bibliologice, 2018)
During 3-5 October 2018, SL USARB librarians participated in the Management Meeting and the Final Conference of the Project "Library Network Support Services: modernising libraries in Armenia, Moldova and Belarus through library staff development and reforming libraries [LNSS]”, a project developed within the Erasmus + program financed by the European Union, which has carried out its work at the Academy of Public Administration and Alecu Russo Balti State University. Event participants visited the Erasmus + Projects Fair, implemented in the USARB, went to the Scientific Library USARB being led through the library's premises by director Elena Harconita. Project beneficiaries have signed a Memorandum of Partnership and Cooperation within the LNSS Consortium.
Keywords: LNSS project; international projects; modernization of libraries